"I wasn't feeling like I belonged in my skin": How self‐identified gay men in the UK experience unhelpful incidents in talking therapy. Issue 4 (8th July 2022) - Televantos, Mike; Strauss, Susan Maise
Abstract: Background: Contemporary psychological research and practice in Western Societies oppose pathologising perspectives about same‐sex attraction. Nonetheless, recent research indicates gay men may still experience unhelpful incidents in talking therapy in relation to their sexual/affectional orientation. Research focusing on how self‐identified gay men (SIGM) experience these unhelpful incidents, however, remains sparse. Aim: The objective of the present study is to offer insight into the phenomenon of unhelpful experiences of SIGM clients in relation to their sexual/affectional orientation. Method: The data were collected through individual, semi‐structured interviews of six SIGM (aged 25–57), describing how they currently experience these unhelpful incidents. This study employed Interpretative Phenomenological Analysis (IPA) to capture the lived experiences and sense‐making of the participants. Findings: The following three Master Themes were identified: (1) Making Sense of Disconnection, (2) A Rejecting Therapy for a Gay Individual, and (3) Understanding the Impact of Unhelpful Incidents Outside Therapy. The unhelpful experiences of SIGM clients appeared to be largely coloured by the sense of disconnection they felt from their therapists. These followed an experience of therapy that they felt did not acknowledge or embrace their individual gay identity. Participants relayed how these experiences impacted their lives outside therapy. Despite the significant and lasting negative impact, however, all imparted a sense of managing to move on to some extent. Conclusions: The present research could encourage therapists and researchers to continue pursuing and embracing helpful ways of working therapeutically with SIGM and other sexual, gender and intersecting identities.